Finding hybridity through fashion design : how to re-wild the foot for a more-than-human future life : a thesis presented in partial fulfilment of the requirements of a Master of Design at Massey University, Wellington, New Zealand - Franklin, Kimberley (Massey University, 2021)
Finding Hybridity through Fashion Design: How to re-wild the foot for a more-than-human future life. My exegesis critically examines and creatively responds to questions of future human evolution and our human relationship with fashion. As fashion designers, I argue, we design the interaction we have, not only with dress but also between ourselves and the world we live in. This has led me to an examination of what a rewilding design methodology and a rewilding design practice can offer to shift our relationships to our dress, to challenge what we perceive as fashion design and how we design (Payne, 9). This exegesis has been written through an autoethnographic understanding given I argue my own mother is beyond human and sits at a hybrid human conjunction. I offer my mother and her relationship with her wheelchair as an example of evolving the human. The Actor Network Theory (ANT) is explored through the narrative example of my mother’s wheelchair in terms of how this actor/actant relationship has structured, mediated, and affected our lives. I further examine fashion and the theory of dress in relation to ANT, considering how fashion and dress may help break down the subject-object divide and positively renegotiate our understanding of lived experiences. I also draw on Jane Bennett’s ‘thing-power’, a concept in which what are commonly perceived as inanimate nonhumans/ objects/ things are in fact vibrant matters that affect our lived experiences and remind us that we are just one being amongst a planet of life (Bennett, 12). Rewilding methodologies are then employed to critique and challenge traditional design thinking in the hopes of producing a morphological footwear design that pushes the boundaries of our being in the world, helping us achieve an empathetic and environmentally sustainable hybridity. I believe that as designers of fashion we must consider designing for the “active corporeal presence” that are human beings and the agentic qualities of the materials used if we are to challenge and change what is fashion design (Bruggeman, 50). This thesis project is my personal journey of the pursuit of a rewilding design methodology and philosophy to establish a future for rewilding design.
Keywords: 330315 Textile and fashion design